Is proactive adaptation to climate change necessary in grazed rangelands? - Ash, Andrew J.; Thornton, Philip K.; Stokes, C.; Togtohyn, C. (Elsevier, 2012)
In this article we test the notion that adaptation to climate change in grazed rangelands requires little more effort than current approaches to risk management because the inherent climate variability that characterizes rangelands provides a management environment that is preadapted to climate change. We also examine the alternative hypothesis that rangeland ecosystems and the people they support are highly vulnerable to climate change. Past climate is likely to become an increasingly poor predictor of the future, so there is a risk in relying on adaptation approaches developed solely in response to existing variability. We find incremental, autonomous adaptation will be sufficient to deal with most of the challenges provided by the gradual expression of climate change in the next decade or two. However, projections of greater climate change in the future means that the responses required are qualitatively as well as quantitatively different and are beyond the existing suite of adaptation strategies and coping range. The proactive adaptation responses required go well beyond incremental on-farm or local actions. New policies will be needed to deal with transformational changes associated with land tenure issues and challenges of some displacement and migration of people in vulnerable parts of rangelands. Even where appropriate adaptation actions can be framed, issues of when to act and how much to act in a proactive way remain a challenge for research, management, and policy. Whether incremental or transformational involving system changes, a diversity of adaptation options will be required in different rangeland regions to enhance social and ecological resilience.